2017
DOI: 10.1007/s00432-017-2534-z
|View full text |Cite|
|
Sign up to set email alerts
|

Exploratory analyses assessing the impact of early tumour shrinkage and depth of response on survival outcomes in patients with RAS wild-type metastatic colorectal cancer receiving treatment in three randomised panitumumab trials

Abstract: PurposeTo report exploratory analyses of early tumour shrinkage (ETS) and depth of response (DpR) in patients with RAS wild-type (WT) metastatic colorectal cancer (mCRC), receiving the first-line treatment in three randomised panitumumab trials. MethodsData from the PRIME (NCT00364013), PEAK (NCT00819780) and PLANET (NCT00885885) studies were included. Median DpR, the proportion of patients achieving ETS ≥ 20% or ≥ 30% at week 8, and the impact of ETS and DpR (including by category) on outcome were analysed. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
(65 reference statements)
3
38
0
Order By: Relevance
“…Of note, it has been reported that both ETS and DpR are associated with improved progression-free survival, OS, and resection rates. 14,15 We also found that changes in ECOG PS were related to whether a treatment response was observed by ETS or DpR, in line with the expectation that all symptoms could affect ECOG PS.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Of note, it has been reported that both ETS and DpR are associated with improved progression-free survival, OS, and resection rates. 14,15 We also found that changes in ECOG PS were related to whether a treatment response was observed by ETS or DpR, in line with the expectation that all symptoms could affect ECOG PS.…”
Section: Discussionsupporting
confidence: 84%
“…30% rates (PRIME: 59% vs. 38%; PEAK: 64% vs. 45%) and greater DpR (PRIME: 54% vs. 46%; PEAK: 65% vs. 46%) than those who received treatment without panitumumab. 14 An association between both ETS and DpR and survival outcomes has also been observed in retrospective and prospective trials of cetuximab. 13,[17][18][19] In the CRYSTAL and OPUS trials, which evaluated cetuximab with and without FOLFIRI and FOLFOX4, respectively, ETS was significantly associated with progression-free survival in both the cetuximab plus chemotherapy and chemotherapy-alone treatment arms.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations